A Reliable Experimental Methodology for the Study of Wind-Turbine Rotor Blade Aerodynamics. (May 2019) - Costantini, M; Fuchs, C; Henne, U; Klein, C; Ondrus, V; Bruse, M; Löhr, M; Jacobs, M
Abstract: The aerodynamic performance of airfoils and blades designed for modern wind-turbine rotors, which have diameters of the order of hundred meters, must be examined at chord Reynolds numbers matching those of practical applications. In general, such high Reynolds numbers cannot be achieved in conventional wind tunnels. Moreover, knowledge on the boundary-layer transition location is essential to evaluate airfoil and blade performance at these flow conditions. This work presents an experimental methodology that can be applied at flow conditions reproducing those of real wind-turbine rotor blades and simultaneously provides aerodynamic coefficients and transition locations. The experimental methodology consists of: the Temperature-Sensitive Paint (TSP) technique for global, non-intrusive and reliable transition detection; conventional pressure measurements for the determination of the aerodynamic coefficients; and the High Pressure Wind Tunnel Göttingen (DNW-HDG) to run the experiments at Reynolds numbers matching those of real applications. The obtained results can be used to verify airfoil and blade performance and to validate numerical predictions. In the present work, the experimental methodology was applied to systematically investigate the aerodynamic performance of an airfoil designed for the mid-span sections of modern wind-turbine rotor blades. The examined chord Reynolds numbers were as high as 12 million and the angle-of-attack ranged from -14° to +20°. The presented methodology was here demonstrated to be mature for productive testing.